The relationship between logistics and organizational performance in a supply chain context - Slobodan Aćimović; Mijušković, Veljko; Dušan Marković; Ana Todorović Spasenić (Serbian Journal of Management, 2022)
The success of managing the distribution of goods, raw materials and the flow of information within a company directly determines the success in managing all operations along the supply chain. Supply chain performance has the status of one of the key organizational performance determinants, while logistics performance is an important determinant of the supply chain performance. The subject of this research is the analysis of impact of logistics performance on organizational performance, with special emphasis on supply chain management performance. Using the analysis of business practice of companies from the territory of the Republic of Serbia, the aim of the research is to crystallize the importance of logistics management for improving the determinants of organizational performance: supply chain management performance, marketing performance and financial performance. The results show that logistics performance is one of the key drivers of generating supply chain management goals, which is directly reflected in the improvement of all categories of organizational performance.